Regime-based debt sustainability analysis: Evidence from euro area economies - Bettina Bökemeier; Benjamin Owusu; Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2022)
This paper empirically studies non-linearities in debt sustainability analysis by resorting to the modern estimation technique of panel smooth transition regression (PSTR). We assess euro area debt sustainability by analysing the reaction of the primary balance to changes in public debt, relative to GDP respectively, in annual frequency from 2000-2019 in a panel framework. The PSTR allows to estimate the existence of a threshold in the behaviour of the reaction function, refrains from the country-wise perspective (pooling) and applies a regime-switching model to detect non-linearities. Data is segregated into different regimes endogenously via a logistics regression. Our results show that there are two different regimes in the euro area: a high and a low debt regime. The estimated reaction coefficient for the low debt regime is statistically insignificant, whereas it is positive and statistically significant for the high debt regime. Further, for a sub-sample of highly indebted economies we find a statistically significant negative (positive) reaction coefficient for the low (high) debt regime.
urn:nbn:de:0070-pub-29632365
Keywords: H63; E62; 330; Debt Sustainability; Fiscal Response Function; Panel Smooth Transition Regression